Childhood during War and Genocide: Agency, Survival, and Representation - Michlic, Joanna Beata; Saal, Yuliya von; Ullrich, Anna (Wallstein Verlag, 2024)
Child survivors of the Armenian Genocide, jewish child survivors of the Holocaust, non-jewish slavic children, and war children of the Second World War EHS Volume 5 presents child-oriented research approaches by scholars from the fields of Holocaust Studies, Genocide Studies, and Second World War History. The authors highlight key concepts of Childhood Studies, arguing that children are historical actors with their own ideas, identity-forming experiences, and agency. The contributions demonstrate the importance of children`s accounts of war and postwar experiences for deeper understanding of the history of war and society in the twentieth century. The volume showcases a variety of children`s voices including child survivors of the Armenian Genocide, Jewish child survivors of the Holocaust, non-Jewish Slavic children, and war children of the Second World War by utilising testimonies from lesser-known archival and oral history collections. Includes: Edita Gzoyan: Forcibly Transferred and Assimilated: Experiences of Armenian Children during the Armenian Genocide. Dieter Steinert: Echoes from Hell: Jewish Child Forced Labourers and the Holocaust. Oksana Vynnyk: Surviving Starvation in Soviet Ukraine: Children and Soviet Healthcare in the early 1930s